Energy community flexibility solutions to improve users’ wellbeing - Mar, Adriana (2022)
Funding Information: Acknowledgments: The authors acknowledge the infrastructure and support of the Department of Electrical and Computer—NOVA School of Science and Technology (FCT NOVA), and of the Centre of Technology and Systems, CTS—UNINOVA. Funding Information: Funding: This research was funded by “Fundação para a Ciência e Tecnologia” (FCT), grant number UIDB/00066/2020. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.